2005
DOI: 10.1186/1465-9921-6-142
|View full text |Cite
|
Sign up to set email alerts
|

Hyperresponsiveness to inhaled but not intravenous methacholine during acute respiratory syncytial virus infection in mice

Abstract: Background: To characterise the acute physiological and inflammatory changes induced by low-dose RSV infection in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 69 publications
1
22
1
Order By: Relevance
“…In the mouse model of RSV infection, whole-body plethysmography has been used to measure airway resistance, and we have found that AHR to inhaled methacholine correlates with pulmonary resistance when measured with more invasive techniques (18,36,46). In our study, we found that antioxidant treatment attenuated RSV-induced AHR, possibly due to a reduction in cys-LT production.…”
Section: Discussionsupporting
confidence: 49%
“…In the mouse model of RSV infection, whole-body plethysmography has been used to measure airway resistance, and we have found that AHR to inhaled methacholine correlates with pulmonary resistance when measured with more invasive techniques (18,36,46). In our study, we found that antioxidant treatment attenuated RSV-induced AHR, possibly due to a reduction in cys-LT production.…”
Section: Discussionsupporting
confidence: 49%
“…The assessment of lung function on anesthetized mice was performed using the flexiVent system (SCIREQ, Montreal, Canada; Refs. 6,38).…”
Section: Methodsmentioning
confidence: 99%
“…If necessary, additional doses of anesthetics were given as required. In addition, the breath rate was set above normal (120 breaths/min) to suppress spontaneous breathing when measuring respiratory mechanics (7,18). Rats were allowed to stabilize on the ventilator for 5 min before the measurements were taken.…”
Section: Animalsmentioning
confidence: 99%